The CDC field epidemiology manual - Rasmussen, Sonja A; Goodman, Richard A (Oxford University Press, 2019)
The manual is the definitive guide to investigating acute public health events on the ground and in real time. Nakladatelská anotace. Kráceno
Keywords: epidemiologické metody; Public Health; veřejné zdravotnictví; Epidemiologic Methods; epidemiologie